1995
DOI: 10.1139/y95-174
|View full text |Cite
|
Sign up to set email alerts
|

Responses of human motoneurons to la inputs: effects of background firing rate

Abstract: The effects of synchronous Ia volleys on the firing probability of repetitively firing human motoneurons were examined at fast and slow firing rates. Ia afferents of either the median or the posterior tibial nerve were stimulated, while single motor unit activity was recorded from the homonymous muscles. Motoneuron responses to the Ia inputs were quantified by measurement of the magnitude of the short latency excitatory peak in peristimulus time histograms (PSTHs). When the stimuli were given at random with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…When the motoneurone is firing tonically, computer simulations (Jones & Bawa, 1997;Matthews, 1999) and experiments (Kudina, 1988;Piotrkiewicz et al 1992;Jones & Bawa, 1995;Olivier et al 1995) have shown that for a test stimulus of given magnitude, the firing probability is greatest at the lowest firing frequencies. There exists some controversy regarding the range of firing frequencies over which this inverse relationship between firing rate and probability of firing will hold.…”
Section: Discussionmentioning
confidence: 99%
“…When the motoneurone is firing tonically, computer simulations (Jones & Bawa, 1997;Matthews, 1999) and experiments (Kudina, 1988;Piotrkiewicz et al 1992;Jones & Bawa, 1995;Olivier et al 1995) have shown that for a test stimulus of given magnitude, the firing probability is greatest at the lowest firing frequencies. There exists some controversy regarding the range of firing frequencies over which this inverse relationship between firing rate and probability of firing will hold.…”
Section: Discussionmentioning
confidence: 99%
“…when the motoneurone membrane was nearing its firing threshold. During this period, motoneurone responsiveness to monosynaptic inputs of cortical or peripheral origin has been found to reach maximal values (Jones and Bawa 1995;Olivier et al 1995). The fact that the firing frequency could not be taken to be responsible for the differences between the motor units' responsiveness was established by the regression analyses between response probability and mean interspike interval performed on a group of slowly contracting, low-threshold motor units and a group of fast-contracting, high-threshold motor units tested at various frequencies in the same experiments.…”
Section: Contribution Of the Ia Monosynaptic Inputs To The Motor Unitmentioning
confidence: 99%
“…This issue has been reinvestigated recently by Jones and Bawa (1995) in the flexor carpi radialis muscle. When electrical stimulations of the muscle afferents were delivered with post-spike delays longer than 60 ms or at random, the responses became smaller as motor unit firing frequency increased.…”
Section: Contribution Of the Ia Monosynaptic Inputs To The Motor Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical stimuli were applied with a Grass S88 stimulator via a SIU5 stimulus isolation unit and a Grass CCU1A constant-current unit. Using a pulse duration of 0.5-1.0 ms, the placement of the electrode and the current were adjusted to obtain a pure H-reflex with no M-wave in the FCR at the lowest stimulus intensity possible (Jones and Bawa 1995). Once the optimal position was obtained, the electrode was secured in place.…”
Section: Methodsmentioning
confidence: 99%